Association between the DASH diet and metabolic syndrome components in Iranian adults. Issue 3 (May 2019) - Ghorabi, Sima; Salari-Moghaddam, Asma; Daneshzad, Elnaz; Sadeghi, Omid; Azadbakht, Leila; Djafarian, Kurosh
Abstract: Purposes: Diet has an important role in the management of chronic diseases. This study aimed to investigate the association of adherence to the dietary approaches to stop hypertension (DASH) diet with metabolic syndrome (MetS) and its components. Methods: This cross-sectional study was performed on 396 Iranian adults, aged ≥18 years. A 147-item food frequency questionnaire (FFQ) was used to assess dietary intakes of participants. Fasting blood sample was obtained to quantify glycemic indicators and lipid profile. Metabolic syndrome was defined based on the guidelines of the National Cholesterol Education Program Adult Treatment Panel III (ATP III). Results: Mean age of study participants was 38.22 ± 9.58 years. A significant inverse association was observed between adherence to DASH diet and odds of MetS (OR: 0.28, 95% CI: 0.14, 0.54); such that after adjusting for energy intake, socioeconomic status and body mass index (BMI), participants in the highest tertile of DASH diet scores were 49% less likely to have MetS (OR: 0.28, 95% CI: 0.14–0.54). Furthermore, adherence to DASH diet was inversely associated with elevated blood pressure (OR: 0.12, 95% CI: 0.05–0.29), high serum triglyceride (OR: 0.53, 95% CI: 0.28–1.00) and low serum HDL-C (OR: 0.51, 95% CI: 0.25–1.01). However, this association was marginally significant for triglyceride and HDL-C. No significant association was found between adherence to DASH diet and abdominal obesity. Conclusion: We found that adherence to DASH was inversely associated with odds of MetS and some of its components including elevated blood pressure, low serum HDL-C and high serum triglyceride.